Practicing Asylum - Gauderman, Kimberly (University of California Press, 2023)
This multidisciplinary volume brings together experienced expert witnesses and immigration attorneys to highlight best practices and strategies for giving expert testimony in asylum cases. As the scale and severity of violence in Latin America has grown in the last decade, scholars and attorneys have collaborated to defend the rights of immigrant women, children, and LGBTQ+ persons who are threatened by gender-based, sexual, and gang violence in their home countries. Researchers in anthropology, history, political science, and sociology have regularly supported the work of immigration lawyers and contributed to public debates on immigration reform, but the academy contains untapped scholarly expertise that, guided by the resources provided in this handbook, can aid asylum seekers and refugees and promote the fair adjudication of asylum claims in US courts. As the recent refugee crisis of immigrant mothers and children and unaccompanied minors has made clear, there is an urgent need for academics to work with other professionals to build a legal framework and national network that can respond effectively to this human rights crisis. “Practicing Asylum is nothing short of groundbreaking. Asylum cases increasingly rest on the quality of country-condition experts’ work.” — HAYDEN RODARTE, immigrant rights attorney “It is rare to read a book that has been written with so much heart and so many insights for academics, attorneys, and advocates alike.” — S. DEBORAH KANG, Associate Professor of History, University of Virginia “Practicing Asylum is a call to action that comes amid an unfolding humanitarian disaster met by a system cruelly stacked against asylum seekers.” — J. T. WAY, Associate Professor of Latin American History, Georgia State University